2022
DOI: 10.1016/j.arthro.2021.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcome and Earlier Return to Activity After Suture Tape Augmentation Versus Broström Repair for Chronic Lateral Ankle Instability? A Systematic Review

Abstract: Improved outcome and earlier return to activity after suture tape augmentation versus Broström repair for chronic lateral ankle instability? A systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
(77 reference statements)
0
12
1
Order By: Relevance
“…Suture tape reinforcement has shown promising results in early return to activity in Broström ankle ligament repair procedures. 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suture tape reinforcement has shown promising results in early return to activity in Broström ankle ligament repair procedures. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Suture tape reinforcement has shown promising results in early return to activity in Brostro ¨m ankle ligament repair procedures. 41 Bachmaier et al 4 provided biomechanical data of soft tissue ACL reconstruction grafts with independent suture tape reinforcement. A comparison was made between 8-mm and 9-mm grafts with suture tape reinforcement showing a synergistic load-sharing configuration.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also have to be compared to outcomes following alternative techniques performing internal bracing by suture tape augmentation. While the patient populations and surgical indication in these studies slightly differ, the reported clinical outcome, with a total FAOS score ranging from 91.7 ± 7.7 to 93.7 ± 6.0 [ 30 , 46 ], indicates that suture tape bracing may be a viable alternative.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Further augmentation with IB has shown excellent results with no major differences in complications. 8 However, Wittig et al 8 noted an increase in occurrence of peroneal nerve and tendon irritation with IB augmentation compared with Broström repair alone in a systematic review of clinical trials, and Pellegrini et al 7 reported 2 implant failures without compromise of construct stability in a prospective study of 13 patients who received IB augmentation of the deltoid ligament. In this report, we present 2 cases of a major complication where placement of the suture anchor during lateral ligamentous IB augmentation violated the subtalar joint, leading to early arthritic changes.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although the IB has a reportedly low complication profile, with the rise in its usage, providers should be aware of potential detrimental complications. 8 Intra-articular placement of suture anchors is a potential complication warned against in the manufacturer surgical technique videos of the IB; however, to our knowledge, this complication has yet to be reported in the literature. 1,3 In the current article, we present 2 cases of suture anchor violation of the subtalar joint during IB augmentation for lateral ligamentous complex repair of the ankle.…”
Section: Introductionmentioning
confidence: 95%